2017
DOI: 10.1128/iai.00803-16
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Proteins BB0405 and BB0406 Are Immunogenic, but Only BB0405 Is Required for Borrelia burgdorferi Infection

Abstract: We recently identified the Borrelia burgdorferi outer membrane protein (OMP) BB0406 and found that the gene encoding this OMP was cotranscribed with the gene encoding the OMP BB0405. Interestingly, BB0405 and BB0406 share 59% similarity and are grouped into the same B. burgdorferi paralogous gene family. Given their overall similarity, it is plausible that both OMPs have similar or overlapping functions in this pathogenic spirochete. BB0405 was recently shown to be required for mammalian infection despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Likewise, during human infection, anti-BB0405 antibodies are not detected either. Interestingly, even though anti-BB0405 polyclonal antibodies are borreliacidal in vitro (52,54), immunization of mice with recombinant BB0405 does not affect any spirochetal burden in infected mice. However, this immunization still induces a long-lasting antibody response, as demonstrated by WB analysis and enzyme-linked immunosorbent assay (ELISA) (53).…”
Section: Is the Vlse System That Omnipotent?mentioning
confidence: 95%
See 3 more Smart Citations
“…Likewise, during human infection, anti-BB0405 antibodies are not detected either. Interestingly, even though anti-BB0405 polyclonal antibodies are borreliacidal in vitro (52,54), immunization of mice with recombinant BB0405 does not affect any spirochetal burden in infected mice. However, this immunization still induces a long-lasting antibody response, as demonstrated by WB analysis and enzyme-linked immunosorbent assay (ELISA) (53).…”
Section: Is the Vlse System That Omnipotent?mentioning
confidence: 95%
“…Also, it has been previously suggested that, during mammalian infection, BB0405 is camouflaged by "abundant neighboring outer membrane proteins" (53). Accordingly, VlsE molecules may well fill the role of these neighboring outer membrane proteins and may explain why anti-BB0405 antibodies are borreliacidal only to in vitro-grown spirochetes (52,54), whose VlsE expression is very low (25).…”
Section: Is the Vlse System That Omnipotent?mentioning
confidence: 99%
See 2 more Smart Citations
“…A downstream application of computational algorithms resulted in mapping of PA epitopes on several surface proteins of B. burgdorferi. Importantly, whenever prior data were available (69,(82)(83)(84)(85)(86)(87)(88), the mapped surface proteins were shown to be immunogenic, capable of inducing protection against wild-type challenge, and critical for B. burgdorferi pathogenesis or growth, all of which are desired characteristics of a strong vaccine candidate (59). Similarly, whenever available, published studies empirically proved the surface exposure of the PA epitope-containing domains of these proteins (59).…”
Section: Figmentioning
confidence: 97%